Effect of Different Concentrations of Kinetin and NAA on Micropropagation of Gardenia Jasminoides - M.S.Duhoky, Mosleh; Rasheed, Khetam A. (Sulaimani Journal for Pure and Applied Sciences, 2010)
The goal of this study was to use plant tissue culture technique in vegetative propagation of Gardenia (Gardenia jasminoides) by using single nodes and shoot tips excised from soft cuttings and treated with different concentrations of growth regulators.The results revealed that the use of different disinfistants was highly effective in reducing cultures contamination. The use of mercuric chloride (0.1%, HgCl2) for 10 minutes was very effective in preventing contamination and gave the highest survival percentage (99%). During the culture of shoot tips at initiation stage, a nutrient medium contained (2 mgl-1 kinetin+ 0.6 mgl-1 NAA) gave the highest values of average number of shoots and leaves and growth length (2.3 shoots/ explant, 2.4 leaves and 1.9 cm respectively).At vegetative multiplication stage, The culture of shoot tips on a nutrient medium containing (3 mgl-1 kinetin) gave the highest values of average number of shoots and leaves (2.9 shoots/ explant, 3.6 leaves respectively).As for growth length, the results revealed that the highest value was achieved by MS medium supplemented by 2 mgl-1 kinetin + 0.1 mgl-1 NAA (3.3 cm). Regarding rooting process, MS medium supplemented by 4 mgl-1 NAA gave the highest average number and length of roots (4.0 roots and 2.50 cm respectively).Also, the medium supplemented by 8 mgl-1 IAA gave the highest number and length of roots (3.40 roots and 3.50 cm respectively). Plantlets obtained were transferred to pots and acclimatized with 95 % success.
Keywords: Gardenia jasminoides; Micropropagation; Tissue Culture; Plant Growth; Regulators